Age mosaic of gut epithelial cells prevents aging - Peizhong Qin; Qi Wang; You Wu; Qiqi You; Mingyu Li; Zheng Guo (Nature Communications)
Abstract Improving gut health by altering the activity of intestinal stem cells is thought to have the potential to reverse aging. The aged Drosophila midgut undergoes hyperplasia and barrier dysfunction. However, it is still unclear how to limit hyperplasia to extend lifespan. Here, we show that early midgut injury prevents the abrupt onset of aging hyperplasia and extends lifespan in flies. Daily transcriptome profiling and lineage tracing analysis show that the abrupt onset of aging hyperplasia is due to the collective turnover of developmentally generated “old” enterocytes (ECs). Early injury introduces new ECs into the old EC population, forming the epithelial age mosaic. Age mosaic avoids collective EC turnover and facilitates septate junction formation, thereby improving the epithelial barrier and extending lifespan. Furthermore, we found that intermittent time-restricted feeding benefits health by creating an EC age mosaic. Our findings suggest that age mosaic may become a therapeutic approach to reverse aging.